Risk Factors for False-Negative and False-Positive Results of Magnetic Resonance Computer-Aided Evaluation in Axillary Lymph Node Staging. Issue 6 (November 2016) - Yun, Seong Jong; Sohn, Yu-Mee; Seo, Mirinae
Abstract : Purpose: The aims of this study were to investigate the false-negative and false-positive results on magnetic resonance (MR) computer-aided evaluation (CAE) in axillary lymph node (ALN) staging and to evaluate the related factors in patients with invasive breast cancer. Methods: From July 2011 to May 2014, 103 invasive breast cancer patients who underwent preoperative MR-CAE were included. False MR-CAE results in ALN staging were compared in terms of clinicopathologic features, baseline mammography, and breast ultrasonography. Logistic regression analyses were used to evaluate independent factors related to false results. Results: For MR-CAE, the false-negative and false-positive results of ALN metastasis were 6.8% and 33.3%, respectively. On multivariate analysis, spiculated tumor margin ( P = 0.016) and positive lymphovascular invasion ( P = 0.020) were associated with false-negative results, and circumscribed tumor margin ( P = 0.017) and negative lymphovascular invasion ( P = 0.036) were associated with false-positive results for ALN metastasis. Conclusions: Tumor margin and lymphovascular invasion are the key factors that affect the false MR-CAE results in ALN staging.